Stability of happiness theories and evidence on whether happiness can change - Sheldon, Kennon M.; Lucas, Richard E. (Academic Press, 2014)
The right to "pursue happiness" is one of the dominant themes of western culture, and understanding the causes of happiness is one of the primary goals of the positive psychology movement. However, before the causality question can even be considered, a more basic question must be addressed: CAN happiness change? Reasons for skepticism include the notion of a "genetic set point" for happiness, i.e. a stable personal baseline of happiness to which individuals will always return, no matter how much their lives change for the better; the life-span stability of happiness-related traits such as neuroticism and extraversion; and the powerful processes of hedonic adaptation, which erode the positive effects of any fortuitous life change. This book investigates prominent theories on happiness with the research evidence to discuss when and how happiness changes and for how long